Peran Guru Pendidikan Agama Islam dalam Meminimalisir Kekerasan pada Siswa SMP Pidie Jaya, Aceh, Indonesia - Muhammad Ar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The school has a function in addition to educating students, it also serves to provide services and guidance so that students avoid bad behavior. However, violence still occurs within the scope of the school, this certainly demands the role and hard work of Islamic Religious Education teachers to minimize the occurrence of violence in students. The purpose of the study was to look at teacher responsibilities, factors and efforts of teachers in minimizing violence in pidie jaya junior high school students. This research uses descriptive qualitative approach and research subjects of principals, Islamic Education teachers and students. Data collection is done by interview. The results showed that, the responsibility of coaching pai teachers in students is carried out through two processes, a) the process of guidance in the classroom and, b) the process of guidance outside the classroom. Factors of occurrence of violence, Internal: a) Unstable emotional state, b) High-risk personality, c) Lack of faith-religiosity. External factors: a) Influence of globalization, b) Family and, c) Social association. As for the efforts made by Islamic Religious Education teachers there are three, preventive (prevention), reprensive and curative, this effort is carried out with approaches in the learning process and outside the learning process.